Banks' financial distress, lending supply and consumption expenditure - H. Evren Damar; Reint E. Gropp; Adi Mordel (Bank of Canada, 2014)
The paper employs a unique identification strategy that links survey data on household consumption expenditure to bank-level data in order to estimate the effects of bank financial distress on consumer credit and consumption expenditures. Specifically, we show that households whose banks were more exposed to funding shocks report significantly lower levels of non-mortgage liabilities compared to a matched sample of households. The reduced access to credit, however, does not result in lower levels of consumption. Instead, we show that households compensate by drawing down liquid assets. Only households without the ability to draw on liquid assets reduce consumption. The results are consistent with consumption smoothing in the face of a temporary adverse lending supply shock. The results contrast with recent evidence on the real effects of finance on firms' investment, where even temporary adverse credit supply shocks are associated with significant real effects.
Keywords: E21; E44; G21; G01; 330; Financial institutions; Credit and credit aggregates; Domestic demand and components